Trend of Climate Change in Nepal: The Case from Morang District (Nepalese Journal of Development and Rural Studies, 2020)
Global circulation model (GCM) projections indicate that the temperature over Nepal will increase between 0.5ºC and 2.0ºC with a multi-model mean of 1.4ºC, by the 2030s and between 3.0ºC and 6.3ºC, with a multi-model mean of 4.70C, by the 2090s. In this context, this paper highlights trend of climate change and its impact on crop production practices of Morang district. The research issues are appraised based on secondary data and document review. This study found that crops production trend has been changed in Morang District. It has decreased from 392330 metric ton in 2068/69 into 318841 metric ton in 2069/70. However, the production of Paddy wheat, maize, oilseed, pulses, potato, vegetables fruits and jute are loss but millet, sugarcane, spices, fish, tea, cardamom and mushroom are increased.Due to climate change, different types of insects are attacking Soil fertility is also declining. Climate change has led to a decline in agricultural production due to floods, inundation of arable lands, changes in the timing of cultivation, and failure of previously planted fertilizer seeds. Therefore, the local and central government must provide subsidy to the marginal farmers through the affirmative attractive policies and programs.